Calcium and Potassium Supplementation Enhanced Growth, Osmolyte Secondary Metabolite Production, and Enzymatic Antioxidant Machinery in Cadmium-Exposed Chickpea (Cicer arietinum L.) - Ahmad, Parvaiz; Abdel Latef, Arafat A.; Abd_Allah, Elsayed F.; Hashem, Abeer; Sarwat, Maryam; Anjum, Naser A.; Gucel, Salih (Frontiers in Plant Science, 2016)
The present work was conducted to examine the role of exogenously applied calcium (Ca; 50 mM) and potassium (K; 10 mM) (alone and in combination) in alleviating the negative effects of cadmium (Cd; 200 μM) on growth, biochemical attributes, secondary metabolites and yield of chickpea (Cicer arietinum L.). Cd stress significantly decreased length and fresh and dry weight of shoot and root, and number of pods and seed yield (vs. control). Exhibition of decreases in chlorophyll (Chl) a, Chl b, and total Chl was also observed with Cd-exposure when compared to control. However, Cd-exposure led to an increase in the content of carotenoid. In contrast, the exogenous application of Ca and K individually as well as in combination minimized the extent of Cd-impact on previous traits. C. arietinum seedlings subjected to Cd treatment exhibited increased contents of organic solute (proline, Pro) and total protein; whereas, Ca and K-supplementation further enhanced the Pro and total protein content. Additionally, compared to control, Cd-exposure also caused elevation in the contents of oxidative stress markers (hydrogen peroxidase, H2O2; malondialdehyde, MDA) and in the activity of antioxidant defense enzymes (superoxide dismutase, SOD; catalase, CAT; ascorbate peroxidase, APX; glutathione reductase, GR). Ca, K and Ca + K supplementation caused further enhancements in the activity of these enzymes but significantly decreased contents of H2O2 and MDA, also that of Cd in shoot and root. The contents of total phenol, flavonoid and mineral elements (S, Mn, Mg, Ca and K) that were also suppressed in Cd stressed plants in both shoot and root were restored to appreciable levels with Ca- and K-supplementation. However, the combination of Ca + K supplementation was more effective in bringing the positive response as compared to individual effect of Ca and K on Cd-exposed C. arietinum. Overall, this investigation suggests that application of Ca and/or K can efficiently minimize Cd-toxicity and eventually improve health and yield in C. arietinum by the cumulative outcome of the enhanced contents of organic solute, secondary metabolites and mineral elements, and activity of antioxidant defense enzymes.